Role of low-intensity pulsed ultrasound on lumbar spondylolysis: a systematic review - Tanveer, Fahad; Arslan, Syed Asadullah; Darain, Haider; Ahmad, Ashfaq; Gilani, Syed Amir; Hanif, Asif (Journal of the Pakistan Medical Association, 2022)
Objective: To systematically review the role of low-intensity pulsed ultrasound on lumbar spondylolysis. Method: Literature search was conducted on PubMed, Embase, CINAHL, Web of Science, PEDro and Scopus databases to identify relevant studies published between 2010 and 2020 by using medical subject headings and applying Booleans, such as low-intensity pulsed ultrasound OR interventional ultrasound AND lumbar spine OR lumbar region AND spondylolysis OR stress fracture. Unpublished studies were hand-searched in the journals, abstracts of conferences were reviewed, and citation index was used for searching experts in the field and then contacting them for information. Studies included were the ones that had at least one of the following outcomes: bone union rate, treatment period to bone union and time to return to previous activities. Results: Of the 243 studies identified, 228(94%) were full text articles and only 2(0.8%) studies were critically appraised for qualitative synthesis based on bone union rate, treatment period to bone union, and time to return to previous activities. Conclusion: Low-intensity pulsed ultrasound was found to be effective for bone union and a useful therapy for quick return to playing sports in patients with lumbar spondylolysis. Key Words: Lumbar region, Spondylolysis, Interventional ultrasound, Systematic review.